Energy and exergy analysis of R600a as a substitute for R134a in automotive air conditioning system - Simbolon, Luga Martin; Arman, Muhammad; Sumeru, Kasni; Setyawan, Andriyanto; Sukri, Mohamad Firdaus (Penerbit Akademia Baru, 2024)
Until now, R134a is still used as a working fluid in automotive air conditioning (A/C) even though it has a very high global warming potential (GWP), which is 1430. Refrigerant R600a is an alternative working fluid as a substitute for R134a in automotive (A/C). This environmentally friendly substitute refrigerant is also expected to produce a better system performance, for which it is necessary to analyse energy and exergy. During work, each AC component generates friction, heat loss, and pressure drop which causes irreversibility in each component. The irreversible quantity of each component is calculated by exergy analysis. Because automotive A/C is driven by engine rotation, its performance is also affected by engine rotation. In this study, the engine rotation to be evaluated is 1000, 1500, 2000, 2500, and 3000 rpm. The evaporating and condensing temperatures of automotive A/C in this study were 5oC and 45oC, respectively. Based on the energy analysis it was found that replacing R134a with R600 enhanced COP, for example at 2000 rpm for R134a and R600a respectively were 3.59 and 3.69, or an increase in COP of about 3%. Based on the exergy analysis, the greatest irreversibility occurred in the compressor, namely 72.1% and 78.6% for R134a and R600a, respectively, for 2000 rpm. This means that there is a potential to enhance the COP improvement using R600a by reducing the irreversibility on the compressor.